2002
DOI: 10.1002/chin.200228157
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Benzimidazole‐4,7‐diones as Inhibitors of Protozoal (Toxoplasma gondii) Purine Nucleoside Phosphorylase.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…[1][2][3][4] Heterocyclic compounds containing the quinone group represent an important class of biologically active molecules. 5 In vitro assays showed that several 2,3-disubstituted 1,4naphthoquinones are as effective as the clinically used antifungal drugs fluconazole and amphotericin-B. [6][7][8] It was also reported that 2-amino-1,4-naphthoquinone showed promising antimalarial activity in the bioassay.…”
mentioning
confidence: 99%
“…[1][2][3][4] Heterocyclic compounds containing the quinone group represent an important class of biologically active molecules. 5 In vitro assays showed that several 2,3-disubstituted 1,4naphthoquinones are as effective as the clinically used antifungal drugs fluconazole and amphotericin-B. [6][7][8] It was also reported that 2-amino-1,4-naphthoquinone showed promising antimalarial activity in the bioassay.…”
mentioning
confidence: 99%